Exploring the relationship between the health-related quality of life and coping strategies Utilizing the FACT-B and the Brief COPE Scale among female breast cancer patients in the Western Cape, South Africa - Vogel, Steyn Lodewyk (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.